MEMAKNAI WATUGUNUNG DAN OEDIPUS SANG RAJA SEBAGAI MITOS TENTANG WAKTU YANG MELAMPAUI WAKTU - Couteau, Jean (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractIt is very interesting to compare Oedipus and Watugunung myths. Both of them have a similar narrative basic structure. Yet, they are different in meaning. One hand, the myth of Oedipus symbolizes the West anthropocentrism with the â Oedipusâ figure as a prototype of West human who is separated from the cosmos, rational, and âfreeâ but he is undermined by blindness/ blank. In other hand, the myth of Watugunung can be said as one of determiners of Bali/ Java cosmocentrism with the Watugunung figure as a prototype of human who attempts to live in a harmony with the cosmos rhythm. He is not âfreeâ but he feel enlightened.Thus, âblindnessâ and âenlightenmentâ, which are presented in the two narratives, are two points which differentiate among point of view of Greek/ West culture and Bali/ Java culture.Keywords: Watugunung myth, Oedipus myth.